Pharmacological Properties and Standardization of Ngoc Linh Ginseng using Ultrasonic-Assisted Extraction - Nguyễn Ngọc Mai Thảo; Trung Phung-Van; Nguyen Tan Thuong (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2025)
This study aims to evaluate the pharmacological potential and standardize the bioactive compounds of Ngoc Linh Ginseng (Panax vietnamensis) as a candidate phytopharmaceutical. The study was conducted throughout 2024 using a multidisciplinary approach, including ultrasonic extraction, chemical analysis, and pharmacological tests. Samples were collected from the Kon Tum and Quang Nam mountains, Vietnam, then extracted by the Ultrasonic-Assisted Extraction (UAE) method using ethanol-water solvents. The total saponin content obtained was analyzed using High Performance Liquid Chromatography (HPLC), resulting in a level of 28.5% with the identification of the main ginsenosides Rg1 and Re. Pharmacological activity was tested in vitro on LPS-induced RAW 264.7 cells, showing a decrease in pro-inflammatory cytokine production by up to 50% and strong antioxidant activity with an IC50 value of 25 µg/mL. In vivo tests on Wistar rats showed a hepatoprotective effect against liver damage caused by a high-fat diet. These results support the potential of Ngoc Linh Ginseng as a candidate for plant-based therapy. Further studies are recommended to explore the pharmacokinetics, clinical efficacy, and optimization of extraction techniques to expand its therapeutic applications.